Penerapan Media Ular Tangga untuk Meningkatkan Pemahaman Siswa dalam Mata Pelajaran PKN Kelas V SDN Timbang - Farhan, Miftahul; Yulianengsih, Neng Lia (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to measure the influence of snake and ladder media development in PKN learning on students' learning understanding in theme 2 of rights and obligations material in class V of SDN Timbang. This study uses a type of Quasi Exerimental Design research with a posttest-only control group design. In this study, the population is all students in grade V of SDN Timbang in Cigandamekar district, while the sample is 21 students in class VA and 22 in class V-B. The average posttest results in the control class were 69, and the average score in the experimental class was 86. The average experimental class increased by 12.05. Based on the results of the calculation using SPSS 29.00, it is known that the tcount value (3,111) > ttable (2,073) and the significance value of 0.003 < 0.05, it can be concluded that the use of snake and ladder media in PKN learning has an effect on the learning understanding of grade V students at Timbang State Elementary School, Cigandamekar District, Kuningan Regency